Effect of Plasma Quenching Parameters on Hardened Layer Properties in Railroad Wheels - Azamat Kanayev; Amangeldy Kanayev; Aliya Moldakhmetova (Tribology in Industry)
This research investigates the effect of quenching current, nozzle-to-surface distance, plasma-forming gas flow rate, and rate of cooling on both plasma torch travel speed (treatment speed) and nozzle diameter. Cooling rates were calculated for various quenching currents based on heat transfer theory. Results show that the relative significance of primary plasma selective quenching parameters remains consistent for both hardened zone depth and width. Notably, the effect of quenching current on hardened zone depth significantly exceeds that of other parameters, highlighting its critical role for optimizing railroad wheel performance. We propose a novel method for controlling the mechanical properties of the hardened surface through regulating wheelset rotational speed during quenching. This approach has the potential to significantly improve the wear resistance and lifespan of railroad wheels, leading to substantial cost savings for the railway industry.